Evaluation of Thoracic Extracardiac Findings in Patients Undergoing Multidetector Computed Tomography Coronary Angiography in Alzahra Hospital, Isfahan, Iran, during 2015-2016 - Maryam Farghadani; Fatemeh Momeni; Mohammad Momeni; Roya Azad; Nasim Ahmadpoor (مجله دانشکده پزشکی اصفهان, 2017)
Background: The aim of our study was to evaluate the prevalence of accidental extracardiac findings in multidetector computed tomography (MDCT) angiography of coronary arteries.